Welcoming in the Family Health Strategy: perspectives of people with disabilities in the rural context - Taís Cristiane Lenz; Marta Cocco da Costa; Isabel Cristina dos Santos Colomé; Andressa de Andrade; Neila Santini de Souza; Jaqueline Arboit (Universidade Federal de Santa Maria, 2020)
Objective: to analyze the perceptions of people with physical disabilities living in the rural context about the welcoming provided by the Family Health Strategy teams. Method: qualitative study, developed in six cities in Rio Grande do Sul, Brazil, whose participants were 13 people with physical disabilities. The production of information took place from January to May 2019 through semi-structured interviews, analyzed by thematic modality. Results: welcoming was related to fondness, affection, relationship of trust, dialogue and closeness with professionals, as well as resolvability of demands or referral to other services. Nevertheless, they listed difficulties regarding the availability of medications, exams, medical care and scheduling of care. Conclusion: despite the efforts of the professionals working in the teams to welcome people with physical disabilities living in the rural context and meet their demands, the centralization of care in biological issues and the limitations of accessibility and access to health services are revealed.